Effect Of Temperature And Electric Field On Polysilicon Gettering Of Copper Impurities In Silicon Wafer - Choong, Chwee Lin (2006)
In this project, a parametric study was conducted on the performance of polysilicon coating for the gettering of copper impurities in silicon wafers of different dopants and concentrations.